Sams Teach Yourself SQL in 21 Days, Fourth Edition - Stephens, Ryan; Plew, Ronald (Sams, 2002)
Sams Teach Yourself SQL in 21 Days, Fourth Edition provides a sold foundation in understanding the fundamentals of SQL (Structured Query Language). SQL is the query language used by relational databases such a Oracle, Microsoft Access, and Microsoft SQL Server. The new edition covers object-oriented programming with SQL, ODBC, JDBC, embedded SQL, accessing remote databases, and constructs. All new examples based on an open source database such as MySQL enhance this new edition by making the examples readily useable for readers.